Judgment on the merits of the International Court of Justice of January 31, 2024, case Ukraine vs Russian Federation - O. A. Kiseleva (Правоприменение, 2024)
The subject. The number of authors who consistently try in their works to “bury” international justice, as well as international law itself, behind the ideas of politicization, bias and unenforceability, has grown significantly today. The political and legal developments of modern international law should still be assessed comprehensively and in detail. First of all, legal events are the is Judgment on the merits of the International Court of Justice of January 31, 2024, case of Application of the International Convention for the Suppression of the Financing of Terrorism and of the International Convention on the Elimination of All Forms of Racial Discrimination (Ukraine vs. Russian Federation).Materials and methods. This research carried out a scientific analysis of the Judgment on the merits of the ICJ dated January 31, 2024. The subject of the study also included other law enforcement acts of the International Court of Justice in this case and in other cases, as well as normative acts of international law.Discussion. The judgment on the merits of the UN International Court of Justice dated January 31, 2024 was one of the most expected and unexpected for many. It is an ambiguous event that requires multifactor analysis. The author analyzed the procedure for considering this dispute, the stated subject and basis of the dispute in conjunction with the decisions of the Court itself on jurisdiction, and assessed the adopted final decisions on the merits of the dispute. It is safe to say that for Russia this decision of the Court is in many ways positive. The positions of the Court in the examined act allow us to draw conclusions not only on the issues of the dispute itself, on the merits of which it was decided, but also regarding the advisability of preserving international justice, which has shown viability and independence.The main results and conclusions. The author analyzes the case review process, the subject of the dispute, which was declared by the applicant and actually considered by the Court, in conjunction with the judgments of the Court on the issue of jurisdiction, and the author gave a legal assessment of the final judgment on the merits of the case. It is safe to say that this Court,s judgment has a positive meaning in many aspects for Russian Federation. The positions of the Court in the act examined allow us to draw conclusions not only on the issues of the case itself, on the merits of which it was rendered, but also on the expediency of preserving international justice, which has shown viability and independence.In addition, the International Court limited itself to proving Russia's guilt in only two minor episodes of international legal violations of the International Convention for the Suppression of the Financing of Terrorism of 1999 and of the International Convention on the Elimination of All Forms of Racial Discrimination of 1965. The Court avoided from orders for damages.